Critical Discourse Analysis of Norman Fairclough on Media Coverage of Free Nutritious Meals Program - Nadiya, Nadiya; Putikadyanto, Agus Purnomo Ahmad (International Journal of Multidisciplinary Approach Research and Science, 2026)
This study aims to examine the discursive construction of the Free Nutritious Meals (MBG) program in Kompas.com. Using a qualitative approach and Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA), this study focuses on textual, discursive, and social practices in two Kompas.com news reports: “Targeting Zero Cases of MBG Food Poisoning by 2026, BGN: God Guarantees” (January 8, 2026) and “Chamber of Commerce: MBG Program Has the Potential to Boost Economic Growth” (January 15, 2026). The analytical framework conceptualizes language as a non-neutral social practice embedded with power relations and ideology. The findings reveal that both articles construct the MBG program through two distinct discursive formations. First, a technocratic-religious discourse that combines policy rationality with symbolic legitimacy through the narrative of “God guarantees.” Second, an economic-productivist discourse that frames MBG as an instrument of economic growth by stimulating market demand. Third, at the ideological level, the discourse reflects the integration of state interests, market forces, and cultural values in shaping public perceptions of the MBG program. This study contributes to critical media discourse studies by integrating technocratic, religious, and economic discourses within a single analytical framework, particularly in the context of contemporary public policy coverage in Indonesia.